Does Stigma Inhibit Labor Force Participation of Young Millennials Who Receive Housing Assistance?. Issue 1 (March 2017) - Haley, Barbara A.
Abstract : Of an estimated 6.8 million households in the United States headed by young adults, aged 19–25, 5 percent receive housing assistance that is funded by the U.S. Department of Housing and Urban Development (HUD). This research looks for evidence in the 2011 American Housing Survey that the stigma associated with residence in HUD‐assisted housing has translated into low self‐efficacy and the "why try" response to becoming economically self‐sufficient. In 2011, a majority of these young householders, 58 percent, participated in the labor force, with household median incomes at 96 percent of the poverty line. Forty percent of householders with less than good health or disability participated in the labor force. The vast majority was also parenting. Small families were the norm. An estimated 526, 000 children under age 18 lived in assisted housing headed by these young millennials. Of these, 158, 000 children were under age 5 and living in households headed by a single adult who was not a labor force participant. Logistic regression was used to find whether there were any statistically significant predictors of labor force participation at the 0.10 level. Good health and no disability of the respondent (OR = 3.3, CI = 1.5–7.4) and educational attainment of some college (OR = 3.2, CI = 1.0–10.2) were statistically significant for the entire sample. Each additional adult in the household also increased (OR = 1.9) the odds of labor force participation by the household head (CI = .9–3.7). For households headed by a single adult, residence in the Midwest Census Region depressed labor force participation (OR = .32, CI = .10–1.00). We conclude that the discovery of these statistically significant predictors suggests that the stigma of living in assisted housing does not create such low self‐efficacy that labor force participation is avoided. Assisted housing reduces the burden on shelters and foster care systems as well as provides a significant safety net for workers who are unable to earn a living wage.